PELUANG, TANTANGAN DAN STRATEGI ZAKAT DALAM PEMBERDAYAAN EKONOMI UMAT - Siti Zumrotun (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
The obligation of zakat in Islam is the most effective and strategic way to develop into an important instrument in improving the welfare of poor people. Zakat is able to empower the economy of the poor people. The potential of zakat can be function optimally and efficiently if zakat management institutions have qualified strategy to face many obstacles or classic constraints which are still maintained by the management of zakat. Management skills, accountability, integrity, and mandate are the principal capital in managing zakat. In addition, utilization of zakat and mentoring or coaching through mustahik are also very important matters. Therefore, zakat management institutions should continue to perform variety of strategies to achieve the purpose of zakat in changing mustahik to become muzaki. The strategies of zakat management are make the habit of paying zakat, creative and smart in collecting zakat, creative form of distribution, qualified human resources, and make the programs which focus on blueprint for the development of zakat.